Selection of Optimum Exponential Smoothing Parameters with Golden Section to Forecast Rainfall in East Kutai Regency - Sa’diyah, Lita Vindiyatus; Wahyuningsih, Sri; Hayati, Memi Nor (EKSPONENSIAL, 2024)
The exponential smoothing method is one method that can be used to forecast time series data by smoothing the data. In this research, the method used is exponential smoothing with one smoothing parameter from Brown. The data used is the amount of rainfall in East Kutai for the period January 2017 to December 2021. The purpose of this study was to obtain the optimum parameter value of the exponential smoothing method using the golden section method to obtain MAPE values and obtain forecasting results for the amount of rainfall in East Kutai Regency for the period January to March 2022. From the results of the analysis, smoothing parameters was obtained optimum in Double Exponential Smoothing (DES) of 0.3924052 and Triple Exponential Smoothing (TES) of 0.1995108. The results showed that forecasting the amount of rainfall with the DES method had a MAPE of 37.9061200% and the TES method had a MAPE of 39.4323800%. The DES method is a better method than the TES method to forecast the amount of rainfall in East Kutai Regency.